2019
DOI: 10.1186/s13244-019-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

The validity and applicability of CAD-RADS in the management of patients with coronary artery disease

Abstract: Background: The coronary artery disease reporting and data system (CAD-RADS) is designed for a uniform standardization of coronary computed tomography angiography (CCTA) reporting and further management recommendations of coronary artery disease (CAD). This study aimed to assess clinical validity, applicability, and reproducibility of CAD-RADS in the management of patients with CAD. Methods and results:A single-center prospective study included 287 patients with clinically suspected or operated CAD who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Since CAD-RADS was introduced, many studies have demonstrated the prognostic value for MACEs and the diagnostic performance of CAD-RADS for predicting CAD (12,20). A recent study in Prospective Multicenter Imaging Study for Evaluation of Chest Pain (12) demonstrated that CCTA findings associated with future MACEs include traditional stenosis categories of the coronary artery, vulnerable plaque, and higher CAD-RADS category.…”
Section: Discussionmentioning
confidence: 99%
“…Since CAD-RADS was introduced, many studies have demonstrated the prognostic value for MACEs and the diagnostic performance of CAD-RADS for predicting CAD (12,20). A recent study in Prospective Multicenter Imaging Study for Evaluation of Chest Pain (12) demonstrated that CCTA findings associated with future MACEs include traditional stenosis categories of the coronary artery, vulnerable plaque, and higher CAD-RADS category.…”
Section: Discussionmentioning
confidence: 99%
“…CTA is the most commonly used modality for aortic evaluation. The accuracy and hence use of CTA for other vascular applications like coronary artery imaging is also expanding [11]. CT is fast, noninvasive, widely available, and allows evaluation of entire aorta with very high (nearly 100%) sensitivity and specificity for the diagnosis of aortic pathologies [2,4,12].…”
Section: Main Textmentioning
confidence: 99%
“…As a result, we recommend conducting more studies to confirm or contradict our cut-off value as recommended before in prior research. 21 …”
Section: Discussionmentioning
confidence: 99%
“…As a result, we recommend conducting more studies to confirm or contradict our cutoff value as recommended before in prior research. 21 CACS can be assessed at a low radiation dosage, which would be less harmful to low-risk individuals. If the CACS is 0, CCTA may not be necessary, 22 which agrees with Bittner et al 23 They reported no cases of obstructive CAD assigned as CAC-DRS 0.…”
Section: Discussionmentioning
confidence: 99%